ANALISIS PENGARUH BIAYA OPERASIONAL TERHADAP KINERJA KEUANGAN PT. PLN ( Persero ) - Wulandari .; Nurhayati .; An Putra Ramadhan (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2020)
Financial institution or company considers that return on assets is one of the most important ratios because this ratio is related to the sustainability and stability of each company or financial institution. In addition, this financial ratio is used to measure a company's ability to generate sufficient profits. high in each period and comes from investment activities. In addition, companies also need to pay attention to factors that can affect the return on assets. In this study aims to find or find out the effect of operational costs and finansial perfomance on return on assets partially. This research was conducted at PT.PLN (persero) Tbk Public Corporation and used documentation data collection and study literature. Data analysis techniques used in this study are simple linear regression, determination, simple correlation coefficient and t test. and in this study the researchers obtained research results that operational costs and operating income had no effect and were not significant to return on assets.